Транспорт анионов Cr(VI) через неорганический ионит и нанокомпозиционную керамическую мембрану - Беляков, В.Н.; Дзязько, Ю.С.; Василюк, С.Л.; Рождественская, Л.М. (Видавничий дім "Академперіодика" НАН України, 2009)
Дослiджено перенос анiонiв Cr(VI) у системi гiдрогель гiдратованого дiоксиду цирконiю керамiчна мембрана, яка модифiкована наночастинками ксерогелю цього iонiту. Розроблено метод визначення рухомостi iонiв у фазi iонiту, який враховує роль мембрани як сорбцiйного бар’єру, iї концентрацiйну поляризацiю та електричний опiр шару iонiту. За нашими висновками, одним з основних факторiв, що визначає транспорт iонiв у системi, є опiр композицiйної мембрани. Визначений коефiцiєнт дифузiї Cr(VI) у фазi iонiту — 2,6 · 10ˉ¹² м² · сˉ¹. Transport of Cr(VI) anions in the system, which involves hydrogel of hydrated zirconium dioxide and a ceramic membrane modified with nanoparticles of xerogel of this ion-exchanger, is investigated. The method for the determination of ion mobility in the ion-exchanger phase, which takes a role of the membrane as a sorption barrier and its concentration polarization and electric resistance into consideration, has been developed. It is shown that the main factor, which determines the ion transport in the system, is the composite membrane resistance. The Cr(VI) diffusion coefficient in the ion-exchanger phase (2.6 · 10ˉ¹² m² · sˉ¹) has been evaluated.